Green Light: On YCl[WO4] as Host Material for Luminescence Active Tb3+ Cations. Issue 24 (26th November 2018) - Schustereit, Tanja; Netzsch, Philip; Höppe, Henning A.; Hartenbach, Ingo
Abstract : Coarse, colorless and transparent single crystals as well as single phase powder of YCl[WO4 ] were yielded by the reaction of Y2 O3, YCl3, and WO3 in evacuated silica ampules at 850 °C for six days, utilizing a fivefold excess of YCl3 with respect to the stoichiometric ratio as flux. The title compound crystallizes isotypically to the RE Cl[WO4 ] representatives for RE = Gd – Tm in the monoclinic space group C 2/ m ( a = 1022.41(3), b = 722.91(2), c = 684.34(2) pm; β = 107.455(3)°; Z = 4). By doping the title compound with about 1 % Tb 3+ cations, bright green luminescence is observed upon irradiation with UV light. Investigations of the excitation and emission spectra at room temperature as well as 77 K reveal a slight shift in the O 2– → W 6+ LMCT transition towards shorter wavelengths upon reducing the temperature. This charge transfer transition can be used as sensitizer for the Tb 3+ luminescence, however, the 5 D3 state of the latter is not reached by this excitation. This is possible by exciting the 7 F6 → 5 G6 transition, which causes the emissions from the aforementioned 5 D3 level to intensify, thus causing a blue shift of the emission. Abstract :